Pembuatan Tepung Mocaf (Modified Cassava Flour) Sebagai Upaya Optimalisasi Pemanfaatan Singkong pada Kelompok Tani - Elda Nazriati; Sri Wahyuni; Herisiswanto Herisiswanto; Rofika Rofika; Zulharman Zulharman; Rita Endriani (Asosiasi Dosen Akuntansi Indonesia, 2021)
Cassava has great potential to be developed into a carbohydrate-based food industry commodity. The large harvest of cassava requires utilization into a more durable product with a higher selling value. One effort that can be done is making mocaf flour (modified cassava flour). The purpose of the service activity is training in the manufacture and packaging of mocaf flour in the SiAkang farmer group. The activity was preceded by a Focus Group Discussion (FGD) to explore the potential use of cassava and its problems. Furthermore, counseling was carried out to get to know mocaf flour, its manufacture, and its use followed by the practice of making and packaging mocaf flour. The results of the activity are in the form of increasing knowledge and skills of farmer groups in processing cassava into mocaf flour, mocaf flour products which have a higher selling value than cassava, and appropriate technology in the form of guidelines for making mocaf flour.